Mitochondrial Epigenetics and Environmental Health: Making a Case for Endocrine Disrupting Chemicals. (10th August 2020) - Zhou, Zheng; Goodrich, Jaclyn M; Strakovsky, Rita S
Abstract: Recent studies implicate mitochondrial dysfunction in the development and progression of numerous chronic diseases, which may be partially due to modifications in mitochondrial DNA (mtDNA). There is also mounting evidence that epigenetic modifications to mtDNA may be an additional layer of regulation that controls mitochondrial biogenesis and function. Several environmental factors (eg, smoking, air pollution) have been associated with altered mtDNA methylation in a handful of mechanistic studies and in observational human studies. However, little is understood about other environmental contaminants that induce mtDNA epigenetic changes. Numerous environmental toxicants are classified as endocrine disrupting chemicals (EDCs). Beyond their actions on hormonal pathways, EDC exposure is associated with elevated oxidative stress, which may occur through or result in mitochondrial dysfunction. Although only a few studies have assessed the impacts of EDCs on mtDNA methylation, the current review provides reasons to consider mtDNA epigenetic disruption as a mechanism of action of EDCs and reviews potential limitations related to currently available evidence. First, there is sufficient evidence that EDCs (including bisphenols and phthalates) directly target mitochondrial function, and more direct evidence is needed to connect this to mtDNA methylation. Second, these and other EDCs are potent modulators of nuclear DNA epigenetics, including DNA methylation and histone modifications. Finally, EDCs have been shown to disrupt several modulators of mtDNA methylation, including DNA methyltransferases and the mitochondrial transcription factor A/nuclear respiratory factor 1 pathway. Taken together, these studies highlight the need for future research evaluating mtDNA epigenetic disruption by EDCs and to detail specific mechanisms responsible for such disruptions.